Carnival organised by undergraduates receives good response - Borneo Post, (KK) (Borneo Post (kk), 2011)
LAHAD DATU: Students of Universiti Malaysia Sabah (UMS) and Universiti Utara Malaysia (UUM) in collaboration with the Lahad Datu District Council (MDLD) organized a Sabah Students Carnival (KARSIS), held over four days starting from June 5 at Dataran Palma here.